First you need to change the denominators so they're the same:
(11/14) * (3/3) = 33/42
(-16/21) * (2/2) = -32/42
Therefore,
33/42 - (-32/42) = 33/42 + 32/42
= 65/42
= 1 23/42
2007-01-16 12:00:42
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
Step 1: 11/14+16/21 Minus a negative makes a positive
Step 2: 11/14(3)+16/21(2) Multiply to get same denominators
Step 3: 33/42 +32/42
Step 4: 65/42 Add them together
DONE
2007-01-16 20:01:25
·
answer #2
·
answered by Jared H 1
·
0⤊
1⤋
When you see two negative signs like this, change it to + + because subtracting a negative is the same as adding a positive.
So 11/14 + (+ 16/21) = 33/42 + 32/42 = 65/42 or 1 and 23/42
2007-01-16 20:02:00
·
answer #3
·
answered by SharonYJ 2
·
0⤊
1⤋
11/14 - (-16/21) = 11/14 + 16/21
= 33/42 + 33/42
= 65/42
= 1 23/42
2007-01-16 19:59:09
·
answer #4
·
answered by (: 2
·
0⤊
1⤋
11/14 - (-16/21)
= 11/14 + 16/21
=33/42 + 32/42
=65/42
=1 23/42
2007-01-16 19:58:57
·
answer #5
·
answered by danjlil_43515 4
·
0⤊
1⤋
first, find a common denominater, which would be 42 in this case
put both fractions into that common denominator by multiplying both the top and the bottom by the factor
(3/3)(11/14) - (2/2)(-16/21)
=(33/42) - (-32/42)
=(33/42) + (32/42)
add the numerators gives
=65/42
2007-01-16 19:59:08
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
11/14 - (-16/21)=
11/14+16/21= <== two - cancels out so = +
1 23/42 <== added!
2007-01-16 19:57:24
·
answer #7
·
answered by Michelle 1
·
0⤊
1⤋
11/14 - (-16/21)
33/42-(-32/42)
65/42
2007-01-16 19:59:21
·
answer #8
·
answered by roger h 1
·
0⤊
1⤋
-- = +
so rewriting with common denominator:
11/(7x2) + 16/(7x3) = 11(3)/(7x2x3) + 16(2)/(7x3x2)
= (33+16)/42 = 49/42 = (7x7)/(7x6) = 7/6
2007-01-16 20:02:38
·
answer #9
·
answered by kellenraid 6
·
0⤊
0⤋
First, 11/14=231/294 -16/21=-224/294
-224/294 - 231/294= -7/294!
-7/294
I hope I could help!
2007-01-16 20:04:03
·
answer #10
·
answered by Alex 5
·
0⤊
0⤋